2006
DOI: 10.1038/sj.gt.3302852
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of HIV-1 replication by simian restriction factors, TRIM5α and APOBEC3G

Abstract: Old World monkey TRIM5a targets incoming human immunodeficiency virus type 1 (HIV-1) viral capsid, whereas the apolipoprotein B mRNA-editing enzyme-catalytic polypeptide-like (APOBEC)3 family hypermutate/degrade viral sequences. Here, we show the potentials of simian TRIM5a and APOBEC3G as therapeutic sequences for AIDS gene therapy. Both rhesus and African green monkey (agm) TRIM5a efficiently restrict HIV-1 vectors with divergent Gag from different HIV-1 subtypes. Human T cells genetically engineered to expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 38 publications
1
15
0
Order By: Relevance
“…The restrictive properties of TRIM5α have been proposed as the basis of anti-viral therapies [1,2,8,10,49]. Our results showing effective AgmTRIM5α-mediated restriction of HIV-1 and SIV mac239 in CD4 + T cells are consistent with the use of the TRIM5α restriction mechanism as an anti-HIV/SIV approach.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The restrictive properties of TRIM5α have been proposed as the basis of anti-viral therapies [1,2,8,10,49]. Our results showing effective AgmTRIM5α-mediated restriction of HIV-1 and SIV mac239 in CD4 + T cells are consistent with the use of the TRIM5α restriction mechanism as an anti-HIV/SIV approach.…”
Section: Discussionsupporting
confidence: 88%
“…In contrast, single-round infectivity assays with pseudotyped defective viruses or viral vectors have found that rhTRIM5α strongly (>70- 95%) restricts HIV-1 infection, while AgmTRIM5α weakly (~60%) restricts SIV mac , with gorilla TRIM5α (gorTRIM5α) having a stronger effect (~90%) [22]. Despite a large body of infection experiments, only a few studies have examined TRIM5α restriction using wild-type viruses in cell-free replication assays [8,10,18,30,48,49]. …”
Section: Introductionmentioning
confidence: 99%
“…While selected by virus infections of the past, the strategies that primates have deployed to cope with lentiviruses, and an understanding of how such adaptations constrain virus fitness, may be exploited as novel therapeutic strategies to stem modern pandemics in humans. For example, the introduction of HIV-specific restriction factors into human cells is a burgeoning avenue for antiviral gene therapy [77][78][79]. However, the vast potential for viruses to counter-evolve in the face of genetic innovations of their hosts means that a combinatorial approach to gene therapy may prove most successful.…”
Section: Looking Backwards To Move Forwardmentioning
confidence: 99%
“…These factors potentially restrict the permissivity of HIV-1-based lentiviral vectors in certain nonhuman primates, especially rhesus macaques, which provide an extensively utilized preclinical model for evaluating the safety and potential efficacy of viral vector strategies for gene therapy approaches to human disease. Among these restriction factors, tripartite motif-containing 5 isoform-␣ (TRIM5␣) and apolipoprotein B mRNA-editing catalytic polypeptide 3G (APOBEC3G) have both been shown to restrict HIV-1 infection and in combination may potentially decrease the transduction efficiency of HIV-1-based viral vectors (31). TRIM5␣ binds to the HIV-1 capsid (hCA) to initiate E3 ubiquitin ligasemediated degradation and prevent viral replication (37).…”
mentioning
confidence: 99%